Professional orientation in university school-service: an experience report of internship - Pacheco, Orjana de Oliveira; Ribeiro, Larissa Aparecida; Medeiros, Júlia Bonilha (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 39 No 76 (2023): Publicação Contínua, 2023)
The Professional and Vocational Orientation (PVO) is a process that helps people with their professional choice, making it easier to acquire knowledge about oneself and regarding the labor market. The goal of this article is to present an experience report of two trainees during their last year of the Psychology course in the internship of PVO, which is also a University Extension project. Two teenagers have participated on the individual PVO process, with weekly sections offered by the School - Service University of Psychology and supervised by an expert professor. Considering it as an educational and clinic strategy, the main tool used was the interview and other auxiliary tools in order to help the reflection process. Two phases made the intervention: the reflexive one, which aims to stimulate the patient to think about issues related to one’s values, interests, family, school experience, and a second informative one that intends to get information about professions, job market and university. The service protocol was structured in eight steps: Diagnostic, Self-Concept, Life History, School Experience, Labor Market, Choice Prerequisites, Professional Reality and Decision Act. The results showed that the patients in the end of the process improved their self-knowledge, reflected about their professional future and obtained information about desired professions. Furthermore, the internship process contributed to gain knowledge and experience for both trainee students by employing the theoretical knowledge, as well as the maturation of this process importance and the professional action based on ethical posture outlook.